2022
DOI: 10.3390/e24020172
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Statistical Entropy in Some New Approaches for the Description of Biosystems

Abstract: Some problems of describing biological systems with the use of entropy as a measure of the complexity of these systems are considered. Entropy is studied both for the organism as a whole and for its parts down to the molecular level. Correlation of actions of various parts of the whole organism, intercellular interactions and control, as well as cooperativity on the microlevel lead to a more complex structure and lower statistical entropy. For a multicellular organism, entropy is much lower than entropy for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…We treat aging as a physical phenomenon within the framework of the approach to the problem of describing the degradation of systems. This study can be seen as a continuation of our work that uses the concept of entropy to describe processes in biosystems [5]. Note that here, we follow the Schrödinger principle, which implies that a biological system in a time-stable state requires a constant influx of negative entropy (negentropy); however, Entropy 2023, 25, 1067 2 of 13 in addition, in this paper, we consider changes in entropy itself in the body due to slow degradation processes.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…We treat aging as a physical phenomenon within the framework of the approach to the problem of describing the degradation of systems. This study can be seen as a continuation of our work that uses the concept of entropy to describe processes in biosystems [5]. Note that here, we follow the Schrödinger principle, which implies that a biological system in a time-stable state requires a constant influx of negative entropy (negentropy); however, Entropy 2023, 25, 1067 2 of 13 in addition, in this paper, we consider changes in entropy itself in the body due to slow degradation processes.…”
Section: Introductionmentioning
confidence: 91%
“…Accordingly, it can be estimated by the rate of glucose metabolism (see also [27][28][29]). Note that in [5], the kinetic model of inhomogeneous spatial relaxation describes this process. The second process is a slow degradation with a characteristic time T = Nτ, where N is a very large number, τ is the time of a characteristic metabolic reaction, and T is the average lifetime of the animal.…”
Section: Degradation Processes In An Open Nonequilibrium Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has shown that allosteric interactions expand the ability of biological systems to store information [ 3 ]. It has also been demonstrated that cooperative interactions lead to an entropy reduction in the system [ 4 ]. In particular, the cooperation between the subunits of ion channels during nerve impulse generation potentiates the ability of neurons and nerve networks to process information [ 5 ].…”
Section: Introductionmentioning
confidence: 99%